Closed Bernoulli lines with finite buffers: real-time performance analysis, completion time bottleneck and carrier control. Issue 7 (3rd July 2021) - Jia, Zhiyang; Dai, Yaping; Chen, Jingchuan
Abstract : Based on the deployment of the new manufacturing strategies (e.g. smart manufacturing), real-time performance analysis, continuous improvement and efficient production management of flexible production systems are with great importance to be investigated. Relevant studies on the serial lines and assembly systems are obtained in recent years. We study real-time performances of closed production lines in this paper. Specifically, the system is assumed to have Bernoulli machines, finite buffers and finite carriers. By using Markovian approach, exact mathematical model for the system under consideration as well as the formulas to calculate the system's transient-based real-time performances are derived. For estimating the performances of a closed line under finite production run-based operation, we propose an approximation method with high accuracy and computational efficiency. Then, completion time bottleneck of the closed line is discussed. Finally, to illustrate the effectiveness of the method, a closed Bernoulli line with carrier control during production is studied.